Hidrocefalus - Case Report - Ćuprić, Mirjana; Veljović, Mirjana; Aničić, Ana; Despotović, Mile; Milojković, Jelena; Stojković, Ivan; Adamović, Ana (Medical Word, 2024)
Hydrocephalus is a pathological condition with many variations which is always characterized by an increase in cerebrospinal fluid that is or has been under increased pressure, and it can occur at any age. It is displayed as different neurological and psychiatric conditions. The most important symptoms in adults are dizziness, cognitive decline, dementia, gait apraxia, and problems with bladder control. This paper presents the case of an elderly person with hydrocephalus. A 74-year-old male patient contacted the doctor of the Healthcare Center because of dizziness, instability when walking or climbing stairs. There is also forgetfulness, poor concentration, and weaker urination control. Orientation neurological examination showed a wide-based gait, with positive Romberg’s sign with eyes closed. He was referred to a neurologist with a questionable diagnosis of vertigo syndrome R 42.0. After neurological and radiological examinations, the diagnosis of communicating, normotensive hydrocephalus was confirmed and the patient underwent neurosurgical intervention. The therapeutic approach to this condition depends on age, clinical findings, and comorbidities and is determined individually for each patient. Surgery takes the main place in therapy because by installing a shunt, a rapid reduction of symptoms is achieved. The role of the selected doctor is to implement all aspects of treatment and care based on anamnestic data, and clinical examination according to the diagnostic algorithm, to improve the functional status and quality of life of these patients and their families.